TEACHING ENGLISH IN PRESCHOOL EDUCATION - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
: the article discusses the problem of instructing English to preschool learners. In order to have a conclusion and grant recommendation on the problem, the literature in the sphere have been studied and the results of research have been provided.